HUBUNGAN KESEPIAN DENGAN DEPRESI YANG DIMODERATORI OLEH RELIGIUSITAS PADA ANAK YATIM PONDOK ANAK YATIM (PAY) AS SALMAN MALANG - Ega Yahya Fadillah (PSIKODIMENSIA, 2017)
Depression generally occurs due to certain life events. Depressed teens tend to experience loneliness, sadness and disappointment in their life. This study aims to determine the relationship between loneliness and depression with the religiosity as the moderator variable. The subjects of this study are 10-13 year old teenagers in “As-Salman” Orphanage in Malang City as many as 32 people. This study uses quantitative methods using UCLA Loneliness scale version 3 to measure loneliness, Beck Depression Inventory (BDI) to measure depression, and Religious Orientatiosn Scale-Revised (ROS-R) to measure religiosity in children. The method of analysis uses Moderated Regression Analysis. The results of the analysis show that there is a direct influence between loneliness and depression in teenagers. Result of correlation coefficient is equal to p = 0,008